2013
DOI: 10.1111/jocn.12386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spiritual intelligence, emotional intelligence, psychological ownership and burnout on caring behaviour of nurses: a cross‐sectional study

Abstract: Healthcare providers must consider the relationships between these factors in their continuing care and incorporation of these in the nursing curricula and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
162
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(179 citation statements)
references
References 58 publications
12
162
0
5
Order By: Relevance
“…They found a consistent inverse relationship between emotional control and management as dimensions of emotional intelligence and stress and burnout. Kaur, Sambasivan, and Kumar's (2013) study show a statistically significant relationship was found among emotional intelligence and stress and burnout. They concluded that developing emotional intelligence may help diminish burnout when chronic stress is experienced.…”
Section: Introductionmentioning
confidence: 76%
“…They found a consistent inverse relationship between emotional control and management as dimensions of emotional intelligence and stress and burnout. Kaur, Sambasivan, and Kumar's (2013) study show a statistically significant relationship was found among emotional intelligence and stress and burnout. They concluded that developing emotional intelligence may help diminish burnout when chronic stress is experienced.…”
Section: Introductionmentioning
confidence: 76%
“…Th e study by Light Irin and Bincy suggests that the stress management interventions are eff ective in reducing job stress among critical care nurses 14 . Th e study by Devinder et al explored other perspectives of nursing care and the results showed that nurses with high emotional intelligence understood their own feelings and the feelings of the others, knew how to manage themselves and deal successfully with the others, and responded eff ectively to work demands 15 . As a…”
Section: Discussionmentioning
confidence: 99%
“…Through these three dimensions, burnout can consequently lead to further negative outcomes such as decreased motivation, increased negative attitudes and behaviors in the workplace, and reduced job performance (Kaur, Sambasivan, & Kumar, 2013).…”
Section: Organizational Commitment the Next Outcome I Consider Is Ormentioning
confidence: 99%